Shareholders’ Value Creation and Market Capitalization – A Case Study of Automobile Industry in India - Singh, Pradeep Kumar (Journal of Contemporary Research in Management (JCRM), 2013)
Abstract In the last two decades the discussion on shareholders’ value creation and its measurement has drawn much attention in the corporate as well as in the academic world. Old traditional methods are criticised for having low correlation with shareholders’ value creation. Therefore, there is a need to have new valuation methods to measure the shareholders’ value creation.Apart from EPS, ROI, ROCE the companies are now giving equal importance to the determination of market capitalisation and value creation for the shareholders as part of their fundamental objective of wealth maximization. There are various methods to determine the shareholders’ value creation. The market capitalization method is one of the most important methods because it includes all the factors like financial efficiency, contribution of tangible capital, contribution of intangible assets, brand image and reputation of the company etc. The objective of the study is to examine shareholders’ value creation with the help of market capitalization and to evaluate the contribution of market capitalization in the creation of intangible assets. The main finding of the present study is that in the automobile industry the brands are attracting and retaining customers, resulting in higher market share, higher turnover, higher profitability and maximization of shareholders value. Hero Honda is reporting about EVA and market capitalization to support and justify shareholders value creation and Eicher ltd is also reporting about market capitalization and its impact on shareholders’ value creation. Tata motors, Maruti Ltd, Bajaj Auto and Hero Honda are having higher market capitalization, higher net worth and higher intangible assets; it indicates that higher market capitalization creates higher intangibles which ultimately enhance shareholders value in long run.